The Value Of Corporate Social Responsibility Shariah Banking Programme In The Context Of Islamic Economic Philosophy - Ana Santika; Amit Kumar Chakrabarty (Universitas Islam Darul 'ulum Lamongan, 2026)
AbstractThe implementation of the value of benefit in Corporate Social Responsibility (CSR) by BSI, by looking at it through the lens of Islamic economic philosophy. The concept of benefit value was raised as the basis for BSI in designing their CSR policies and practices. In the context of Islamic economic philosophy, this study examines how the values of benefit, embodied in maqashid al-Shariah, are reflected in the CSR practices of Islamic banking. This study uses descriptive analysis methods and literature to evaluate BSI practices and identify the extent to which the implementation of benefit values is reflected in the policies and activities of CSR practices. The results in this study are: a) Welfare is an important part of CSR in Indonesian sharia banking, which includes criteria for sharia compliance, justice, and public welfare. b) Indonesian Islamic banks have a social responsibility to achieve public welfare, which is in line with the principles of Islamic economics. c) The implementation of CSR in BSI also involves the perspective of Shariah Enterprise Theory, which emphasizes the importance of benefit in business decision making. d) BSI's CSR encourages the domestic economy through the development of MSME Centers in various regions in Indonesia, Aceh, Yogyakarta, and Surabaya as a means to achieve the goals of community benefit and not just an effort to obtain profits. The research findings indicate that BSI, in an effort to integrate the principles of Islamic economics, allocates their resources to support the welfare of society and carry out their social responsibilities taking into account the moral and ethical aspects of business.